Study of Z boson plus jets events using variables sensitive to double-parton scattering in pp collisions at 13 TeV - Tumasyan, Armen (2021)
Double-parton scattering is investigated using events with a Z boson and jets. The Z boson is reconstructed using only the dimuon channel. The measurements are per formed with proton-proton collision data recorded by the CMS experiment at the LHC at √ s = 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1 collected in the year 2016. Differential cross sections of Z+ ≥1 jet and Z+ ≥2 jets are measured with transverse momentum of the jets above 20 GeV and pseudorapidity |η| < 2.4. Several dis tributions with sensitivity to double-parton scattering effects are measured as functions of the angle and the transverse momentum imbalance between the Z boson and the jets. The measured distributions are compared with predictions from several event generators with different hadronization models and different parameter settings for multiparton interac tions. The measured distributions show a dependence on the hadronization and multipar ton interaction simulation parameters, and are important input for future improvements of the simulations.